A novel solar desalination system based on an evacuated tube collective condenser heat pipe solar collector: A thermo-economic and environmental analysis - Nema, Garima; Karunamurthy, K (Frontiers in Mechanical Engineering, 2022)
Solar desalination has captivated consideration to overcome the problem of the scarcity of freshwater, with simple-design, economic, and environment-friendly solutions. This study navigates a novel solar-evacuated glass tube collector integrated with a collective condenser heat pipe system for solar desalination. A newly designed heat pipe array was represented in this work by affixing all the evaporator tube units of the heat pipes to a single condenser unit and was attached to the evacuated tube solar collector. The innovative assembly of the heat pipe provided uniform heating of water and rapid steam generation. The present system acts as a solar collector and as a stand-alone basin for freshwater formation. The performance assessment of the neoteric system was conducted based on half-filled and three-fourth-filled conditions of the water flow pipe kept within the collective condenser heat pipe. The maximum heat pipe temperature recorded during the half-filled state was 156.9°C and 151.48°C in the three-fourth-filled state. The half-filled state of the water flow pipe delivered a total distilled water content of 8,050 ml/day, whereas the three-fourth-filled state delivered 5,925 ml/day of distilled water. The maximum energy and exergy efficiency of the presented system was 19.27% and 3.92%, respectively. The economic minimum unit cost of freshwater by the present system is 4.27 INR, and the payback period is 2.9 years. The present eco-friendly energy system saves 4.25 kWh of electricity and 4.16 × 10−3 tons of CO2 equivalent per year.